The atmosphere as an evangelist of community and fraternity - María Verónica Di Caudo (Universidad Politécnica Salesiana, 2013)
This article highlights the key importance of the evangelical environment itself. Through work with and between youth in parishes, groups and communities, movements, and educational institutions; an atmosphere of testimony, fraternity, faith and good relationships that look at Jesus' example, dignifies a person towards integral processes of spiritual change. Consequently, the option of building an evangelical environment -supported by community and kerygmatic anthropological dimensions- in the pastoral youth service work, cannot stay unconnected from pedagogical and formative issues.